Iodine-coated porous carbon composite catalyst as well as preparation method and application thereof
By uniformly distributing noble metals and transition metals within porous carbon spheres and coating their surfaces with iodine, the problems of slow oxygen reduction and insufficient durability in existing catalysts are solved, achieving a high-efficiency and low-cost improvement in catalytic performance.
Patent Information
- Application Number
- CN202411655209.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-10
AI Technical Summary
Existing proton exchange membrane fuel cell catalysts suffer from problems such as slow oxygen reduction and insufficient durability due to high platinum loading, resulting in high fuel cell costs and difficulty in large-scale commercialization.
Iodine-coated porous carbon composite catalysts are used, in which noble metals and transition metals are uniformly distributed in the porous carbon spheres, and iodine is coated on the surface of the carbon spheres. By adjusting the electronic structure of the noble metals, the adsorption and activation of oxygen molecules are optimized, and the influence of poisoning substances is reduced.
Improve the catalyst's resistance to poisoning and catalytic activity, reduce the amount of precious metals used, enhance the activity and stability of the oxygen reduction reaction, and reduce the cost of fuel cells.
Smart Images

Figure CN119297312A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton exchange membrane fuel cell catalytic material preparation, and in particular to an iodine-coated porous carbon composite catalyst and a preparation method and application thereof. Background Art
[0002] The problems faced by the energy system include unreasonable energy consumption structure, low energy utilization efficiency, multiple constraints on energy supply, backward energy technology, great pressure on carbon emission reduction, and severe environmental pollution. Under the current trend of energy structure transformation, hydrogen energy has attracted widespread attention due to its cleanliness, high efficiency and renewability. Proton exchange membrane fuel cells (PEMFCs) are generally regarded as an ideal energy choice for applications such as electric vehicles and fixed power stations due to their advantages such as low-temperature operation, fast start-up, high specific power output, simple design and convenient operation. Among the catalyst materials of proton exchange membrane fuel cells, catalytic activity and durability are the key factors that determine their performance. However, since high-loaded platinum catalysts can only make oxygen reduction occur slowly, and there is still a problem of insufficient durability, the cost of raw materials and the use process is greatly increased, which greatly limits the large-scale commercial application of fuel cells.
[0003] The advantages of fuel cells as an energy system are their high efficiency, environmental friendliness and wide application prospects, but the high catalyst cost and poor effect are the main problems they face. Therefore, it is of great significance to prepare low-cost catalysts with excellent catalytic performance. Summary of the invention
[0004] In view of these problems, the present invention proposes an iodine-coated porous carbon composite catalyst, characterized in that the composite catalyst includes precious metals and transition metals, the precious metals and transition metals are uniformly distributed in the porous carbon spheres in a single-atom state, and elemental iodine is coated on the surface of the carbon spheres. Furthermore, the noble metal is one or more of platinum, palladium, gold, and iridium, preferably platinum; and the transition metal is one or more of Cu, Co, Zn, Ni, and Mn, preferably Cu.
[0005] Furthermore, the average particle size of the composite catalyst is 1-100 nm.
[0006] The present invention also provides a method for preparing an iodine-coated porous carbon composite catalyst, comprising the following steps: (1) ultrasonically dispersing a noble metal source, a transition metal source, and an organic ligand in a solvent for a certain period of time to obtain a polymer precursor solution; (2) adding a certain amount of sodium formate to the polymer precursor solution obtained in (1), adjusting the pH, ultrasonicating, and allowing to stand; (3) After the precursor solution in (2) is filtered, it is dried in a vacuum drying oven to obtain a powdery substance; (4) calcining the powdered substance described in (3) under an inert atmosphere to obtain a calcined product; (5) The calcined product obtained in (4) is mixed with a certain amount of iodine source, ground thoroughly, and then kept warm in an inert atmosphere for a period of time to obtain a composite catalyst material.
[0007] Furthermore, the noble metal salt includes but is not limited to one or more of the chlorides, acetic acid compounds, and acetylacetone compounds of the noble metal; the iodine source includes but is not limited to one or more of the cetyltrimethylammonium iodide, elemental iodine, and ammonium iodide; the transition metal source includes but is not limited to one or more of the nitrates, chlorides, sulfates, and acetates of the transition metal; the organic ligand may be one or more of 1,3,5-benzoic acid and 2-methylimidazole.
[0008] Furthermore, in step (1), the solvent includes, but is not limited to, one or more of water, methanol, ethanol, isopropanol and N,N-dimethylformamide; preferably, a mixture of ethanol and water in a volume ratio of 1:1.
[0009] Furthermore, during the preparation process, the noble metal source, iodine source, organic ligand, transition metal source and solvent are calculated by weight to be 1 to 3 parts of noble metal source, 10 to 30 parts of iodine source, 80 to 90 parts of organic ligand, 120 to 135 parts of transition metal source, and 15,000 to 18,000 parts of solvent; further preferably, by weight, 1 to 2 parts of noble metal source, 10 to 15 parts of iodine source, 80 to 85 parts of organic ligand, 120 to 125 parts of transition metal source, and 15,000 to 16,000 parts of solvent.
[0010] Furthermore, in step (1), the ultrasonic time is 1-3 h; in step (2), the pH is 3-4, the ultrasonic time is 0.5-1 h, and the mixture is allowed to stand for 10-24 h; in step (3), the drying temperature is 50-100° C., and the drying time is 6-18 h; in step (4), the calcination temperature is 600° C.-1000° C., and the insulation time is 1.5-2.5 h; in step (5), the insulation temperature is 150° C.-250° C., and the insulation time is 2-10 h.
[0011] Furthermore, the inert gas includes at least one of nitrogen, helium and argon.
[0012] The present invention also provides an application of the composite catalyst as described above or the catalyst prepared by the preparation method as described above in a fuel cell.
[0013] The beneficial effects of the present invention are as follows: Iodine coating on the surface of porous carbon catalyst improves the anti-poisoning performance and catalytic activity of the catalyst material. Iodine coating can reduce the direct contact between precious metal catalysts and poisoning substances (such as sulfides), thereby reducing the impact of poisoning substances on the active sites of the catalyst, maintaining the electronic structure of the catalyst, and making it have good stability. At the same time, this coating can also optimize the adsorption and activation of oxygen molecules by adjusting the electronic structure of precious metal atoms, further improving the oxygen reduction reaction (ORR) activity of the catalyst. The application of iodine coating technology in fuel cell catalysts helps to improve the performance and stability of the catalyst and reduce the use of precious metals, which is of great significance for reducing the cost of fuel cells and improving environmental adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the SEM image of the catalyst material prepared in Example 1.
[0015] Figure 2 This is the X-ray diffraction pattern of the catalyst material prepared in Example 1.
[0016] Figure 3 Linear polarization curves of the catalyst material prepared in Example 1 and the catalyst material in Comparative Example 3 in 0.1 M KOH solution under saturated oxygen.
[0017] Figure 4 This is a comparison chart of the mass activity and specific activity of the catalyst material prepared in Example 1 and the catalyst material in Comparative Example 3.
[0018] Figure 5 The chronopotentiometric response diagram of the catalyst material prepared in Example 1 and the catalyst material in Comparative Example 3 relative to the standard hydrogen electrode at 0.5 V. DETAILED DESCRIPTION
[0019] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0020] In the present invention, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0021] Example 1 (1) By weight, 1 part of platinum source, 120 parts of copper salt, and 80 parts of 1,3,5-benzoic acid were ultrasonically dispersed in 15,000 parts of water and ethanol (volume ratio 1:1) solvent for 2 hours; (2) A certain amount of sodium formate was added to the low-platinum HKUST-1 precursor solution obtained in (1), and after adjusting the pH, the solution was ultrasonicated for 0.5 h and allowed to stand for 12 h.
[0022] (3) After the precursor solution in (2) is filtered, it is dried in a vacuum drying oven at a temperature of 80° C. for 10 h; (4) calcining the low-platinum HKUST-1 precursor described in (3) under an inert atmosphere at a calcination temperature of 800° C. for a holding time of 2 h to obtain a powdery substance; (5) The powder obtained in (4) was thoroughly ground with 10 parts of hexadecyltrimethylammonium iodide, and then kept at 200° C. in an inert atmosphere for 5 h to obtain a catalyst material.
[0023] Example 2 (1) By weight, 1 part of platinum source, 120 parts of cobalt salt, and 80 parts of 2-methylimidazole were ultrasonically dispersed in 15,000 parts of water and ethanol (volume ratio 1:1) solvent for 2 h; (2) A certain amount of sodium formate was added to the low-platinum ZIF-67 precursor solution obtained in (1), and after adjusting the pH, the solution was ultrasonicated for 0.5 h and allowed to stand for 12 h.
[0024] (3) After the precursor solution in (2) is filtered, it is dried in a vacuum drying oven at a temperature of 80° C. for 10 h; (4) calcining the low-platinum ZIF-67 precursor described in (3) under an inert atmosphere at a calcination temperature of 800° C. for a holding time of 2 h to obtain a powdery substance; (5) The powder obtained in (4) was thoroughly ground with 10 parts of hexadecyltrimethylammonium iodide, and then kept at 200° C. in an inert atmosphere for 5 h to obtain a catalyst material.
[0025] Example 3 (1) By weight, 1 part of platinum source, 120 parts of zinc salt, and 80 parts of 2-methylimidazole were ultrasonically dispersed in 15,000 parts of water and ethanol (volume ratio 1:1) solvent for 2 h; (2) A certain amount of sodium formate was added to the low-platinum ZIF-8 precursor solution obtained in (1), and after adjusting the pH, the solution was ultrasonicated for 0.5 h and allowed to stand for 12 h.
[0026] (3) After the precursor solution in (2) is filtered, it is dried in a vacuum drying oven at a temperature of 80° C. for 10 h; (4) calcining the low-platinum ZIF-8 precursor described in (3) under an inert atmosphere at a calcination temperature of 800° C. for a holding time of 2 h to obtain a powdery substance; (5) The powder obtained in (4) was thoroughly ground with 10 parts of hexadecyltrimethylammonium iodide, and then kept at 200° C. in an inert atmosphere for 5 h to obtain a catalyst material.
[0027] Comparative Example 1 Compared with implementation case 1, step (5) is not performed and other conditions remain unchanged.
[0028] Comparative Example 2 Compared with implementation case 1, step (2) is not performed and other conditions remain unchanged.
[0029] Comparative Example 3 Commercially purchased Pd / C electrode and Pt / C electrode materials. 3 mg of the final product of Examples 1-3 and Comparative Examples 1-2 was dispersed in 1 mL of a deionized water / isopropanol mixture (volume ratio = 3 / 1), and 15 μL of a 10% Nafion solution was added. The mixture was sonicated for 2 hours to obtain a uniform catalyst ink. For comparison, Pd / C and Pt / C catalyst inks were prepared by sonicating 3 mg of commercial Pd / C or Pt / C with the same amount of Nafion, deionized water, and isopropanol mixture. For ORR measurements, the polarization curves from 1.2 V to 0.2 V versus RHE were tested in 0.1 M KOH solution at a scan rate of 5 mV s-1.
[0030] Table 1 shows the catalytic starting potential, half-wave potential, mass activity, and stability after 12 hours of Examples 1-3 and Comparative Examples 1-3.
[0031]
[0032] Table 1 Figure 1 This is a SEM image of the catalyst material prepared in Example 1. It can be seen from the image that the size is uniform and iodine is coated on the surface of the carbon shell.
[0033] Figure 2 This is the X-ray diffraction pattern of the catalyst material prepared in Example 1. It can be seen from the XRD spectrum that the characteristic peak is located at about 2θ=26.5°, which is the strongest peak of graphitized carbon and is related to the stacking mode of the graphite layer. The peak intensity is proportional to the degree of graphitization, and no obvious platinum peak appears, indicating that the product iodine-coated low-platinum porous carbon has been synthesized.
[0034] Figure 3 The linear polarization curve of the catalyst material prepared in Example 1 in 0.1 M KOH solution under saturated oxygen is shown in FIG. Figure 3 It can be seen that the onset potential (Eonset, 1.0 V) and half-wave potential (E1 / 2, 0.88 V) are higher than those of commercially available Pd / C.
[0035] Figure 4 The mass activity and specific activity of the catalyst material prepared in Example 1 and the catalyst material in Comparative Example 3 are compared. When compared with the standard hydrogen electrode at 0.8 V, the mass activity is 1.25 A mg -1 , which is about 2.4 and 5.2 times higher than commercially available Pt / C (0.53 A mg -1 Pt) and Pd / C (0.24 A mg-1Pd).
[0036] Figure 5 The chronopotentiometry responses of the catalyst material prepared in Example 1 and the catalyst material in Comparative Example 3 relative to the standard hydrogen electrode at 0.5 V show that the catalyst material prepared in Example 1 exhibits excellent ORR stability and maintains a current density of 86% after 12 hours of continuous operation.
[0037] From the experimental data in Table 1, it can be seen that the comparison of the performance of Examples 1-3 shows that the transition metal element copper has the best effect, whether it is the starting potential, half-wave potential, mass activity or stability after 12 hours, it is better than other examples. Preliminary analysis shows that on the one hand, the HKUST-1 polymer prepared by copper has a more uniform particle size distribution, and at the same time, Cu and Pt atoms are chelated in the polymer by the three formic acids in 1,3,5-benzoic acid, so that they are more evenly dispersed in the final material and have more active sites. Therefore, the catalytic activity of the material is the best; It can be seen from Example 1 and Comparative Example 1 that iodine coating can significantly improve the catalytic performance. Iodine coating can reduce the direct contact between platinum and poisoning substances such as sulfides, thereby reducing the impact of poisoning substances on the active sites of the catalyst, maintaining the electronic structure of the catalyst, and making it have good stability. At the same time, this coating can also optimize the adsorption and activation of oxygen molecules by adjusting the electronic structure of platinum atoms, further improving the oxygen reduction reaction (ORR) activity of the catalyst.
[0038] Example 1 and Comparative Example 2 prove that the catalyst performance can be improved after treatment with sodium formate. This is because after the polymer precursor in Example 1 is treated with sodium formate, the polymer morphology can be made more uniform and the particle size can be made more uniform. In this way, after the subsequent carbonization treatment, the prepared catalyst carbon material is not easy to agglomerate, has more active sites, and can improve the catalytic performance.
[0039] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. An iodine-coated porous carbon composite catalyst, characterized in that: The composite catalyst comprises noble metal and transition metal, wherein the noble metal and transition metal are uniformly distributed in the porous carbon sphere in a single-atom state, and elemental iodine is coated on the surface of the carbon sphere.
2. The iodine-coated noble metal porous carbon composite catalyst according to claim 1, characterized in that: The noble metal is one or more of platinum, palladium, gold, and iridium, preferably platinum; the transition metal is one or more of Cu, Co, Zn, Ni, and Mn, preferably Cu.
3. The iodine-coated porous carbon composite catalyst according to claim 1 or 2, characterized in that: The average particle size of the composite catalyst is 1-100 nm.
4. A method for preparing the iodine-coated porous carbon composite catalyst according to any one of claims 1 to 3, characterized in that: The steps include: (1) ultrasonically dispersing a noble metal source, a transition metal source, and an organic ligand in a solvent for a certain period of time to obtain a polymer precursor solution; (2) adding a certain amount of sodium formate to the polymer precursor solution obtained in (1), adjusting the pH, ultrasonicating, and allowing to stand; (3) After the precursor solution in (2) is filtered, it is dried in a vacuum drying oven to obtain a powdery substance; (4) calcining the powdered substance described in (3) under an inert atmosphere to obtain a calcined product; (5) The calcined product obtained in (4) is mixed with a certain amount of iodine source, ground thoroughly, and then kept warm in an inert atmosphere for a period of time to obtain a composite catalyst material.
5. The preparation method according to claim 4, characterized in that: Precious metal salts include but are not limited to one or more of the chlorides, acetic acid compounds, and acetylacetone compounds of precious metals; iodine sources include but are not limited to one or more of cetyltrimethylammonium iodide, elemental iodine, and ammonium iodide; transition metal sources include but are not limited to one or more of the nitrates, chlorides, sulfates, and acetates of transition metals; and the organic ligands may be one or more of 1,3,5-benzoic acid and 2-methylimidazole.
6. The preparation method according to claim 4, characterized in that: In step (1), the solvent includes, but is not limited to, one or more of water, methanol, ethanol, isopropanol and N,N-dimethylformamide; preferably, a mixture of ethanol and water in a volume ratio of 1:
1.
7. The preparation method according to claim 4, characterized in that: During the preparation process, the noble metal source, iodine source, organic ligand, transition metal source and solvent are calculated by weight as 1 to 3 parts of noble metal source, 10 to 30 parts of iodine source, 80 to 90 parts of organic ligand, 120 to 135 parts of transition metal source, and 15,000 to 18,000 parts of solvent; further preferably, calculated by weight as 1 to 2 parts of noble metal source, 10 to 15 parts of iodine source, 80 to 85 parts of organic ligand, 120 to 125 parts of transition metal source, and 15,000 to 16,000 parts of solvent.
8. The preparation method according to claim 4, characterized in that: In step (1), the ultrasonic time is 1-3 hours; in step (2), the pH is 3-4, the ultrasonic time is 0.5-1 hour, and the mixture is allowed to stand for 10-24 hours; in step (3), the drying temperature is 50-100° C., and the drying time is 6-18 hours; in step (4), the calcination temperature is 600° C.-1000° C., and the insulation time is 1.5-2.5 hours; in step (5), the insulation temperature is 150° C.-250° C., and the insulation time is 2-10 hours.
9. The preparation method according to claim 4, characterized in that: The inert gas includes at least one of nitrogen, helium and argon.
10. Use of the composite catalyst according to claims 1 to 3 or the catalyst prepared by the preparation method according to any one of claims 4 to 9 in a fuel cell.
Citation Information
Cited By
Preparation method and application of porous carbon-based iodine-rich catalyst
CN120268425A